Erythropoietin in the Locus coeruleus attenuates the ventilatory response to CO2 in rats - Silva, Carlos A. [UNESP] (2017)
The Locus coeruleus (LC) is a pontine area that contributes to the CO2/pH chemosensitivity. LC cells express erythropoietin (Epo) receptors (EpoR), and Epo in the brainstem is a potent normoxic and hypoxic respiratory stimulant. However, a recent study showed that the intra-cisternal injection (ICI) of Epo antagonist does not alter the hypercapnic ventilatory response in mice. As ICI leads to a widespread dispersal of the product throughout the brainstem, in this work we evaluated the specific impact of Epo in the LC-mediated ventilatory response to CO2 (by whole body plethysmography) in juvenile male Wistar rats. Normocapnic and hypercapnic ventilation were evaluated before and after unilateral microinjection of Epo (1 ng/100 nL) into the LC. To evaluate the long-term effect of Epo, the HcVR was re-evaluated 24h later. Our results show that Epo attenuates the hypercapnic ventilation. We conclude that Epo in the LC tunes the hypercapnia-induced hyperpnea. (C) 2016 Elsevier B.V. All rights reserved.